2020
DOI: 10.3390/molecules25235736
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation Preserves Antioxidant and Antidiabetic Activities of Cactus Acid Fruit Bioactive Compounds under Simulated Digestion Conditions

Abstract: Cactus acid fruit (Xoconostle) has been studied due its content of bioactive compounds. Traditional Mexican medicine attributes hypoglycemic, hypocholesterolemic, anti-inflammatory, antiulcerogenic and immunostimulant properties among others. The bioactive compounds contained in xoconostle have shown their ability to inhibit digestive enzymes such as α-amylase and α-glucosidase. Unfortunately, polyphenols and antioxidants in general are molecules susceptible to degradation due to storage conditions, (temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 58 publications
2
14
1
1
Order By: Relevance
“…In this study, the variation in the inhibitory effect against α-amylase and α-glucosidase enzymes was in agreement with the difference in the antioxidant activity of the of the encapsulated powders using different coating formulations. In consistence with the finding of this study, the literature on the encapsulation of phenolic-rich extracts also showed that the enzyme inhibitory activity of the microcapsules is highly correlated with their antioxidant activity which are attributed to the phenolic content in the samples (Medina-Pérez et al, 2020;Rambaran, 2020).…”
Section: In Vitro Antidiabetic Activities Of Microcapsules Containing...supporting
confidence: 88%
“…In this study, the variation in the inhibitory effect against α-amylase and α-glucosidase enzymes was in agreement with the difference in the antioxidant activity of the of the encapsulated powders using different coating formulations. In consistence with the finding of this study, the literature on the encapsulation of phenolic-rich extracts also showed that the enzyme inhibitory activity of the microcapsules is highly correlated with their antioxidant activity which are attributed to the phenolic content in the samples (Medina-Pérez et al, 2020;Rambaran, 2020).…”
Section: In Vitro Antidiabetic Activities Of Microcapsules Containing...supporting
confidence: 88%
“…Consistent with these findings, the literature on phenolic-rich extracts reveals that enzyme inhibitory activity is highly correlated with antioxidant activity, which has been attributed to the phenolic content in samples. 36,37…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these findings, the literature on phenolic-rich extracts reveals that enzyme inhibitory activity is highly correlated with antioxidant activity, which has been attributed to the phenolic content in samples. 36,37 Principal component analysis (PCA) was used to identify the relationship between the drying temperature, the correlation between extract bioactivities, and the contents of individual compounds. Figure 1 is a representation of the 6 drying treatments for all of the contents of the individual compound and extracts bioactivities.…”
Section: Correlation Analysis and The Principal Component Analysismentioning
confidence: 99%
“…The flavonoids were analyzed according the technique reported by Sancho et al [18] with some modifications Medina-Pérez et al [19] . One gram of honey was diluted (1:10) with methanol (Femont, MX), homogenized and centrifuged at 17,500 × g for 15 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%